Should UI Benefits Really Fall Over Time? - John Hassler; José V. Rodríguez Mora (Institute for the Study of Labor (IZA), 2002)
The issue of whether unemployment benefits should increase or decrease over the unemployment spell is analyzed in a tractable model allowing moral hazard, adverse selection and hidden saving. Analytical results show that when the search productivity of unemployed is constant over the unemployment spell, benefits should typically increase or be constant. The only exception is when there is moral hazard and no hidden saving. In general, adverse selection problems tend to generate increasing benefits, moral hazard problems constant benefits and decreasing search productivity falling benefits.
Keywords: J65; J64; E24; 330; unemployment insurance; moral hazard; adverse selection; Arbeitslosenversicherung; Arbeitslosigkeit; Dauer; Arbeitsuche; Moral Hazard; Adverse Selection; Sparen; Theorie